(untitled) (Panacea Journal of Medical Sciences, 2024)
Aims and Objectives: To evaluate and compare quality of life in pre dialysis (CKD stage4) and patients with End stage renal disease (ESRD) on maintenance hemodialysis and to analyze the correlation of sociodemographic, clinical and laboratory parameters with quality of life. Materials and Methods: This was a cross-sectional study in which 100 pre dialysis(CKD stage4) and 100 ESRD patients on maintenance hemodialysis were enrolled. SF 36 questionnaire was used to assess quality of life. Quality of life was compared between the two groups and the correlation of quality of life with sociodemographic ,clinical and laboratory parameters was assessed. Results: Pre dialysis group had better SF 36 scores than patients on hemodialysis (64.93±13.05 vs. 59.55±13.29 p=0.004). Erythropoietin use, higher albumin and more frequent dialysis emerged as independent predictors of better quality of life. Conclusion: Perceived quality of life was worse for patients on hemodialysis when compared to pre dialysis patients. Use of erythropoietin, higher albumin levels, and more frequent dialysis were independent predictors of better quality of life.